EVALUASI MULTIDIMENSI KEBERLANJUTAN PENGELOLAAN BENIH BENING LOBSTER (PUERULUS) DI PERAIRAN KABUPATEN TULUNGAGUNG BERBASIS RAPID APPRAISAL FOR FISHERIES (RAPFISH) - Susadiana; Lis M Yapanto; Hatim Albasri (Smart Education, 2026)
Abstract: The waters of Tulungagung Regency possess potential for clear lobster seed (BBL), driving high levels of fishing activity for this commodity. BBL management—including harvesting activities—is governed by government regulations that underwent frequent changes between 2021 and 2024. This study aimed to examine BBL management issues in Tulungagung by characterizing BBL utilization, assessing the sustainability status of BBL management, and formulating management strategies. Data were collected through interviews, observation, and documentation. Analysis employed MDS RAPFISH to determine sustainability status and AHP to formulate priority management strategies. The results indicate that BBL fishing activities in Tulungagung are environmentally friendly, utilizing *pocong* nets that comply with the standards set in the Regulation of the Minister of Marine Affairs and Fisheries Number 7 of 2024. RAPFISH analysis classified the sustainability status as